Vibration and damping characteristics of sisal and glass fiber reinforced polyester composite - athishKumar, G; Chandrasekaran, M; Vinod Kumar, T; Vivek, P (International Journal of Engineering and Technology, 2018)
This study aims to evaluate the result of experimental investigation carried out on free vibration characteristics and damping factors of short sisal & glass fiber polyester composite. Composites specimen is fabricated in random fiber orientation using to hand lay-up method by Influence of fiber length (10mm) and weight percentage (5, 10, 15, 20 wt. %) . Studies revealed that increase in the fiber content will in-crease the natural frequency (Hz) and decrease the damping factor is given by the composites having a fiber loading of 20 wt. percentage ranges. The properties were compared with neat polyester. In this work, increasing fiber content increases the natural frequency (Hz) and decrease the damping factors of the composite.Â Â